EFFECT OF PRECURSOR SOLUTION COMBINATION ON BANDGAP ENERGY OF ZNO SYNTHESIZED USING THE HYDROTHERMAL METHOD: PENGARUH KOMBINASI LARUTAN PREKURSOR TERHADAP BANDGAP ENERGY DARI ZNO YANG DISINTESIS DENGAN METODE HIDROTERMAL - Shafa Rahma Cyrilla; Rahmat Setiawan Mohar; Iwan Sugihartono; Maykel Manawan (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
Nanostructure ZnO has been synthesized via hydrothermal method at 95ºC for 4 hours using different combinations of precursor solutions, namely zinc nitrate seng nitrat hexahydrate and ammoniac [NH3], as well as zinc nitrate hexahydrate [Zn(NO3)2·6H2O] and hexamethylenetetramine (HMT) [C6H12N4]. The optical properties were then investigated by scanning X-ray diffraction and UV-Vis Diffuse Reflectance spectrophotometer. The analysis of optical properties is carried out with reference to the reflectance pattern, so that the energy gap of ZnO nanostructures can be determined using the Tauc Plot technique. The Tauc Plot analysis results show that the band gap energy with NH3 precursor (3.09 eV) is lower than that using HMT (3.22 eV).